The critique of psychiatry as we enter the third decade of the 21st century: Commentary on… Critical psychiatry. (December 2020) - Rashed, Mohammed Abouelleil
Abstract : Summary: Critical psychiatry takes the position that 'mental illness' should not be reduced to 'brain disease'. Here I consider whether this particular stance is outdated in light of more recent exchanges on reductionism, which consider questions raised by new mental health sciences that seek truly integrative and specific biopsychosocial models of illness.